Pengaruh Penilaian Prestasi Kerja, Loyalitas, dan Senioritas terhadap Promosi Jabatan pada Karyawan PT. Mikatasa Agung - Duvan Samudra Laisoka; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The aim of this research is to determine the influence of work performance assessment, loyalty and seniority on job promotions for employees in the logistics department of PT MIKATASA AGUNG. This type of research uses a quantitative approach with data sources, namely primary and secondary. Data collection used a questionnaire and the number of samples used was 63 employees with a sampling technique using saturated samples. The analysis tool used is Smart PLS v.4.0.9.7 with the SEM analysis method. The results of this research show that work performance has a significant positive influence on job promotion, Loyalty has an insignificant negative influence on job promotion and seniority has an insignificant positive influence on job promotion.